Antimicrobial Resistance Patterns in Companion Animals: A Multicentre Study - Dr.M.V.Balasubramanyam; Dr. Misbhauddin Khan; Dr. Arti Thakur; Dr Aman Kumar Sharma (Revista Electronica de Veterinaria, 2024)
The objective of this multicentre study was to evaluate the prevalence of AMR in companion animals in different geographical locations. Carried out in conjunction with the veterinary practices and diagnostic laboratories, the survey involved 1,200 animals: 800 dogs and 400 cats with bacterial infections. Specimens such as skin swabs, urine, blood and ear swabs were taken and cultured and identified and their susceptibility to antimicrobials was determined. The average resistance rate was 48% and it was also observed that there are disparities in the different regions. Resistance was higher in the urban regions at 52% as compared to the rural regions at 43%. Resistance patterns were different with the species and higher resistance was observed in dogs (50%) as compared to cats (45%). The following specific pathogens showed significant resistance: Staphylococcus pseudintermedius and Escherichia coli. For example, S. pseudintermedius was 60% resistant to methicillin; E. coli was 50% resistant to ampicillin. The study further showed that AMR rates differ significantly between centres (p < 0. 05) and there are correlations between AMR and animals’ attributes. These results highlight the necessity of developing the regional surveillance of AMR and the targeted interventions in companion animals.